2023
DOI: 10.1038/s41427-023-00478-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanodrug-based eye drops with good penetration properties and ROS responsiveness for controllable release to treat fungal keratitis

Abstract: Fungal keratitis is challenging to diagnose and treat and remains a significant cause of blindness worldwide. The easiest and most common method of drug delivery for patients with fungal keratitis is eye drop administration. However, the therapeutic effect of traditional eye drops is unsatisfactory, largely due to the intrinsic nature of the ocular barriers, which limit drug absorption; the rapid decrease in the drug concentration caused by tears; and the side effects induced by the uncontrolled release of ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…used glycol chitosan as a nanocarrier and 4‐carboxyphenylboronic acid pinacol ester as a ROS‐responsive group to encapsulate antifungal drug, voriconazole and then developed a ROS‐controlled release polymeric nanocarrier (GC‐EB) to treat fungal keratitis. [ 239 ] Unfortunately, the application of ROS‐responsive nanocarriers in FND management is almost a desert. Surprisingly, as an emerged oasis in the desert, Jiang et al.…”
Section: Smart Nanocarrier‐based Nanomedicines For the Treatment Of Fndsmentioning
confidence: 99%
“…used glycol chitosan as a nanocarrier and 4‐carboxyphenylboronic acid pinacol ester as a ROS‐responsive group to encapsulate antifungal drug, voriconazole and then developed a ROS‐controlled release polymeric nanocarrier (GC‐EB) to treat fungal keratitis. [ 239 ] Unfortunately, the application of ROS‐responsive nanocarriers in FND management is almost a desert. Surprisingly, as an emerged oasis in the desert, Jiang et al.…”
Section: Smart Nanocarrier‐based Nanomedicines For the Treatment Of Fndsmentioning
confidence: 99%
“…These include NIMs carrying an agent cross-linked by visible light for corneal regeneration [23] and NIMs carrying peptide-drug conjugates (PDCs) with prolonged bioavailability to synergistically treat inflammation associated ocular disorders [24]. Other NIMs consist of polymeric nanocarriers bearing agents with reactive oxygen species (ROS) controlled release [25] and a versatile hybrid hydrogel. These NIMs have been found to exhibit the spatiotemporal properties allowing for drug release [26] in the treatment of infectious keratitis, and gene delivery by solid lipid NPs (SLNs) to treat X-linked juvenile retinoschisis [27].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution has become one of the key environmental crises, , associated with considerable detrimental human health outcomes. Among air pollutants, ambient fine particles (AFPs, commonly known as fine particulate matter or PM 2.5 ) are gaining increasing attention in public health. Strikingly, emerging studies suggested that the AFP pollution could not only affect the eye surface, such as eye discomfort, aberrant tear morphology, and ocular surface inflammation, but also have indirect adverse effects on the inner structures of eyes through inflammatory cytokines. Liu et al previously reported the presence of black carbon particles at the ocular surface and found a positive association with dry eye disease . AFPs are laden with various pollutants (e.g., heavy meal, polycyclic aromatic hydrocarbons, and pathogens) and will transform once in the biological microenvironment, generating reactive oxygen species (ROS) and bringing unpredicted health risks .…”
Section: Introductionmentioning
confidence: 99%